2020
DOI: 10.1016/j.jhazmat.2020.122871
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-dependent effects on photosynthesis of Solanum lycopersicum L.—An ecophysiological, ultrastructural and molecular approach

Abstract: This study aimed to assess the toxicity of glyphosate (GLY; 0, 10, 20 and 30 mg kg −1 ) in Solanum lycopersicum L., particularly focusing on the photosynthetic metabolism. By combining ecophysiological, ultrastructural, biochemical and molecular tools, the results revealed that the exposure of tomato plants to GLY led to alterations in leaf water balance regulation [increasing stomatal conductance (g s ) and decreasing water use efficiency (WUE i ) at higher concentrations] and induced slight alterations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 68 publications
(98 reference statements)
2
17
0
Order By: Relevance
“…Moreover, and considering that EPSPS is located in chloroplasts [ 55 , 56 ], the main source of O 2 •− in plant cells, the burst of this ROS in GLY-exposed plants suggests, once again, that tomato plants failed to prevent the occurrence of oxidative stress. Accordingly, in our former study, a completely altered ultrastructure of chloroplasts towards GLY treatment was observed [ 45 ], reinforcing that plastid-mediated changes can be overall indicators of GLY-induced stress in plants.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, and considering that EPSPS is located in chloroplasts [ 55 , 56 ], the main source of O 2 •− in plant cells, the burst of this ROS in GLY-exposed plants suggests, once again, that tomato plants failed to prevent the occurrence of oxidative stress. Accordingly, in our former study, a completely altered ultrastructure of chloroplasts towards GLY treatment was observed [ 45 ], reinforcing that plastid-mediated changes can be overall indicators of GLY-induced stress in plants.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, our research group, along with other notable studies [ 12 , 40 , 41 , 42 ], has provided important findings concerning GLY non-target phytotoxicity in important plant species, such as barley ( Hordeum vulgare L.) [ 43 ], alfafa ( Medicago sativa L.) [ 44 ] and tomato ( Solanum lycopersicum L.) [ 10 , 45 ]. However, as well as understanding GLY-associated environmental risks, it is also essential to develop new approaches to increase plant tolerance to this herbicide [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within this perspective, and as previous studies from our research group have shown that soil contamination by GLY can negatively affect the growth and physiology of non-target plant species, such as tomato (Solanum lycopersicum L.) [8,25] and barley (Hordeum vulgare L.) [9], the main objectives of this study were (i) to evaluate the potential protective role of NO in counteracting GLY-induced stress in crops; and (ii) to pinpoint the main physiological and biochemical mechanisms behind NO action in GLY-exposed plants. Since S. lycopersicum (tomato) is one of the most important species worldwide and has been widely used as a model organism for fleshy-fruited plants [26], this species was selected for this study.…”
Section: Introductionmentioning
confidence: 73%
“…Therefore, we can determine the effect of stress factors on plant photosynthesis by measuring photosynthetic pigment contents. Soares et al (2020) showed that under glyphosate stress, the total chlorophyll and carotenoid contents of Solanum lycopersicum L. leaves were decreased. The chlorophyll a, chlorophyll b, and carotenoid contents of foxtail millet were reduced under low light during the grain-filling stage (Yuan et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%